Exploring self-care and cervical cancer prevention attitudes and practices among Moroccan and Pakistani immigrant women in Catalonia, Spain: a comparative qualitative study - Jone G. Lurgain; Hakima Ouaarab-Essadek; Khadija Mellouki; Sumaira Malik-Hameed; Andleeb Sharif; Maria Brotons; Laia Bruni; Paula Peremiquel-Trillas (BMC, 2024)
Abstract Background Self-care and preventive health strategies may trigger health inequities when individuals' cultural values and health beliefs are not fully understood and considered. In the case of cervical cancer (CC) screening programs immigrant women have shown lower attendance compared with native women, which increases the risk of late diagnosis and, consequently, a lower probability of survival. HPV self-sampling for CC screening has been recently added to the World Health Organization's (WHO) list of self-care interventions as a promising tool to reduce this disparity and improve screening coverage. In Catalonia, Spain, the introduction of HPV self-sampling as a part of the new population-based CC screening program, is a significant step. However, there is a lack of research addressing self-care and prevention among immigrant populations in this region. This study aims to fill this gap exploring self-care and prevention attitudes and practices among Moroccan and Pakistani women. Methods We conducted focus groups and individual interviews with 36 Moroccan and 37 Pakistani women in Barcelona, Spain. The topic guide of the focus groups included case vignettes to stimulate the discussion and a semi-structured questionnaire was used for the interviews. Results Our findings show that most Moroccan and Pakistani women do not prioritize self-care and prevention. They seek care for symptom treatment rather than disease prevention. In this sense, they reported not having the habit of doing regular check-ups and their self-care and prevention attitudes and practices seemed to be conditioned by cultural values. The implementation of an effective call and recall system could enhance the engagement of these populations with CC screening services. Conclusion This study provides evidence on how universal concepts of self-care and prevention may not aligned with more collectivist societies, emphasizing the limited applicability and motivation of global self-care interventions guidelines for individuals with different cultural backgrounds and values. Therefore, the successful implementation of CC screening programs or any other self-care intervention requires the adoption of culturally appropriate strategies.